Effects of the different time length of heat treatments in E. coli K12 in raw shelled walnuts - Clemage, Lindsey; Carbajal, A.; Chamraswimonrat, K.; Davis, H.; Coria, A.; Cotton, T.; Coleman, E.; Jones, Cassandra K.; Trinetta, Valentina (My University, 2017)
Introduction: Escherichia coli (E. coli) are found in the environment, in animals, and are found on everyday food items. E. coli bacteria are very diverse and can live in different environments which can cause many problems in our food supply. E. coli can grow and survive in low water activity food like walnuts, and are also known to survive thermal heat treatments. Purpose: This study focuses on the effects of thermal heat on E. coli on walnuts and the duration of time it takes to kill the gram negative bacteria. Methods: The oven was set to 280⁰F, treatment one was a ten minute duration and treatment two was a twenty minute duration. The raw, shelled walnuts were inoculated with 107 CFU/ml E. coli concentration, divided into 10 gram bunches and were treated to the thermal heat. Once both treatments were applied to the inoculated walnuts they were placed in a stomacher bag for one minute. Three dilutions were applied; 10-2, 10-3, 10-4, and were placed on three different media plates; PCA, PDA, McConkey, and placed incubator at 95⁰F, for optimum growth. During the three day experiment a total of 270 plates, with a negative control, positive control, treatment one and treatment two were plated. Results: During the duration of this experiment there was no growth for the negative control. The positive control showed a two log reduction during the three days. Both treatments showed a decline in E. coli growth. The p-values for PCA <.0001, PDA < .001, and McConkey < .0002, all show that these treatments were significant. Therefore, using thermal heat Killed E. coli, and we reject the null hypothesis. Significance: The results of this study demonstrated the presence of E. coli on walnuts was killed with treatments one, and two.
Keywords: Fall 2017